2018
DOI: 10.21037/ajo.2018.09.02
|View full text |Cite
|
Sign up to set email alerts
|

Permeatal ‘push through’ myringoplasty in the Northern Territory: a prospective cohort

Abstract: Background: The permeatal cartilage 'push through' tympanoplasty is a safe and effective technique that has previously been shown to be beneficial in a variety of settings. This study examines its efficacy in a population with high proportions of Indigenous Australians who live in remote areas and have a high burden of chronic suppurative middle ear pathology. Methods: Multi-centre prospective case series. Two hundred and forty-one patients underwent transcanal "push-through" myringoplasty in the Northern Terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Reported graft uptake rate ranges between 84.4 and 97.4 per cent in patients who underwent endoscopic push-through myringoplasty. 4,8,13,14 Kim et al . reported a perforation closure rate of 91.3 per cent in patients undergoing modified butterfly-inlay cartilage (comprising one side perichondrium as in our study) myringoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported graft uptake rate ranges between 84.4 and 97.4 per cent in patients who underwent endoscopic push-through myringoplasty. 4,8,13,14 Kim et al . reported a perforation closure rate of 91.3 per cent in patients undergoing modified butterfly-inlay cartilage (comprising one side perichondrium as in our study) myringoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In studies reporting butterfly-inlay and push-through cartilage myringoplasty outcomes, a significant improvement in ABG values was observed without a remarkable difference in both techniques. 1,4,7,8,1416 According to a recent study comparing the functional results of fascia and cartilage graft, Mouna et al . reported that there was no significant difference between fascia and cartilage grafts in terms of auditory functions.…”
Section: Discussionmentioning
confidence: 99%